2019
DOI: 10.11648/j.hss.20190702.14
|View full text |Cite
|
Sign up to set email alerts
|

From the Four Generations Cohabitation Family to the Dink Family: The Evolution of Chinese Young People's Family Concept

Abstract: China's family planning policy has achieved remarkable results in controlling the excessive growth of population, but it has also caused a series of problems, such as labor shortage, consumption depression and so on, especially the impact on the traditional family values of young people. Young people do not want to have more children, or even one child, which will have a huge impact on the development of Chinese society. This paper probes into the reasons of the evolution of family values of young people in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In China, DINK families mainly appear in large cities, such as Beijing and Shanghai. A survey in 2002 showed that the proportion of DINK families in Shanghai was 12.4% (Wu & Yin, 2019). Second, destiny belief, which refers to the belief that fate is predestined, is deeply rooted in Chinese culture (He, Tang, Zhu, & Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In China, DINK families mainly appear in large cities, such as Beijing and Shanghai. A survey in 2002 showed that the proportion of DINK families in Shanghai was 12.4% (Wu & Yin, 2019). Second, destiny belief, which refers to the belief that fate is predestined, is deeply rooted in Chinese culture (He, Tang, Zhu, & Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%